Promoting Safe Sleep, Tobacco Cessation, and Breastfeeding to Rural Women During the COVID-19 Pandemic: Quasi-Experimental Study - Carolyn R Ahlers-Schmidt; Christy Schunn; Ashley M Hervey; Maria Torres; Jill Elizabeth V Nelson (JMIR Publications, 2021)
BackgroundSafe Sleep Community Baby Showers address strategies to prevent sleep-related infant deaths. Due to the COVID-19 pandemic, these events transitioned from in-person to virtual. ObjectiveThis study describes outcomes of transitioning Safe Sleep Community Baby Showers to a virtual format and compares outcomes to previous in-person events. MethodsParticipants from four rural Kansas counties were emailed the presurvey, provided educational materials (videos, livestream, or digital documents), and completed a postsurvey. Those who completed both surveys received a portable crib and wearable blanket. Within-group comparisons were assessed between pre- and postsurveys; between-group comparisons (virtual vs in-person) were assessed by postsurveys. ResultsBased on data from 145 in-person and 74 virtual participants, virtual participants were more likely to be married (P<.001) and have private insurance (P<.001), and were less likely to report tobacco use (P<.001). Both event formats significantly increased knowledge and intentions regarding safe sleep and avoidance of secondhand smoke (all P≤.001). Breastfeeding intentions did not change. Differences were observed between in-person and virtual meetings regarding confidence in the ability to avoid secondhand smoke (in-person: 121/144, 84% vs virtual: 53/74, 72%; P=.03), intention to breastfeed ≥6 months (in-person: 79/128, 62% vs virtual: 52/66, 79%; P=.008), and confidence in the ability to breastfeed ≥6 months (in-person: 58/123, 47% vs virtual: 44/69, 64%; P=.02). ConclusionsAlthough both event formats demonstrated increased knowledge/intentions to follow safe sleep recommendations, virtual events may further marginalize groups who are at high risk for poor birth outcomes. Strategies to increase technology access, recruit priority populations, and ensure disparities are not exacerbated will be critical for the implementation of future virtual events.